(untitled) (Journal of Bangladesh Institute of Planners, 2010)
Unplanned urbanization defying building codes are continuously increasing the earthquake vulnerability of citizens of Dhaka city. So, existing situation requires the assessment of earthquake vulnerability by identifying those factors contributing to vulnerability. This paper attempts to employ such assessment to identify and analyze the contribution of different factors to compare ward. 37 (Begunbari) and 69 (Nimtoli) of new and old Dhaka respectively. It applies Analytical Hierarchical Process (AHP) for determining the weight and priority of the vulnerability factors’ contribution to the life of individuals. Using GIS, vulnerability index (VI) of different factors is calculated by defining an ordinal scale and overall vulnerability index maps of study areas are prepared representing the vulnerability of individual buildings. Analyses reveal that Nimtoli (mean VI is 3.06) is more vulnerable than Begunbari (mean VI is 2.77). It is also observed that soil category of Nimtoli is better than that of Begunbari but in Nimtoli about 74% buildings are old, 63% buildings are pucca and 75% buildings have less than 100 m2 area causing to increase vulnerability. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 103-112